2001
DOI: 10.1097/00005537-200101000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Activity of Common Reagents for Insect Foreign Bodies of the Ear

Abstract: Many commonly available reagents may be used to kill or immobilize insect foreign bodies of the ear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…(USA) similarly report beads and insects, particularly cockroaches, to be the commonest foreign bodies in the external auditory canal from 273 combined paediatric and adult patients. 12 Our experience was different from these series. We found the majority of foreign bodies in adult patients to be the cotton wool tips of cotton buds.…”
Section: Discussionmentioning
confidence: 68%
“…(USA) similarly report beads and insects, particularly cockroaches, to be the commonest foreign bodies in the external auditory canal from 273 combined paediatric and adult patients. 12 Our experience was different from these series. We found the majority of foreign bodies in adult patients to be the cotton wool tips of cotton buds.…”
Section: Discussionmentioning
confidence: 68%
“…Cockroaches were the most commonly specified insect foreign bodies (78%). In nearly 38% of insect foreign body cases, the offending organism was not specified [3].…”
Section: Discussionmentioning
confidence: 99%
“…The best solution from Leffler et al is microscope immersion oil (mineral oil) [4], with similar effect from olive oil or baby oil. Ticks are exception and resistant to various solutions [3]. Using lidocaine can occasionally lead to serious vertigo which require admissions [5].…”
Section: Discussionmentioning
confidence: 99%
“…In available studies on adult aural foreign body, the object is mostly cotton wool of cotton buds, flying insects or silicone ear plugs 2 . In some studies, cockroaches have been found as a common foreign body both in adults and children 3 .…”
Section: Introductionmentioning
confidence: 99%